The relationship between corporate social responsibility and firm performance: a study of South African listed companies - Mukoki, Paul Shepherd (My University, 2016)
A growing number of institutional investors that are adopting corporate social responsibility (CSR) philosophy are playing a crucial role in influencing listed companies to adopt and address CSR issues. CSR is defined as “…a concept whereby companies integrate social and environmental concerns in their business operations…” (European Commission, 2010). CSR is now widely accepted as a way of doing business in the contemporary environment. It is evident in companies that are spending large sums of money, time and effort on satisfying various stakeholders’ requirements for responsible behaviour. Despite the growing pressure on companies to become socially responsible, the direct benefits of CSR contribution to firm performance remain questionable. From existing literature the relationship between CSR and firm performance have pointed to mixed results (Gladysek & Chipeta, 2012; Aggarwal, 2013). This study examines the relationship between CSR performance and firm performance using the CSRHub sustainability indexes as proxy for CSR performance. The firm performance measures of firm value (Tobin’s Q) and financial accounting performance (return on assets) were used. Annual data of firms from the Johannesburg Stock Exchange (JSE) from year 2009 to 2012 was analysed using the Multiple Regression Analysis techniques. The study revealed that significant and positive relationship exists between CSR/environmental performance and firm value of listed South African companies. The study concluded that there is no significant relationship between firm performance and the other components of CSR such as community relations, employment relations, and governance. The relatively small sample size of the listed companies, some missing values on the sample data and the shorter time period on the study are the main limitations acknowledged in this report. In the overall, the study provides important insights for understanding the contribution of CSR and its disaggregated components to firm performance.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree in Master of Commerce (50% course work)
Keywords: Corporate social responsibility; Corporate social performance; Firm performance; Return on investment (ROI); Tobin's Q